A flexible pattern reconfigurable antenna for WLAN wireless systems. Issue 6 (13th April 2019) - He, Xiaoxia; Gao, Peng; Zhu, Ziqiang; You, Sicen; Wang, Peng
ABSTRACT: A novel flexible pattern reconfigurable antenna for WLAN wireless system is proposed. The reconfigurable antenna is fed by a microstrip, and consists of a circular monopole patch, three ship-shaped parasitic patches, a planar ground and two parallel symmetrical parasitic branches embedded with two PIN diodes. The antenna achieves two-state pattern reconfigurability by controlling the on and off of two PIN diodes to change the director. The antenna has a bandwidth of 2.40-2.48 GHz and is capable of steering the beam in the direction 30°, 330° in the azimuthal plane. Meanwhile, the antenna works at two states with the same band. Finally, the bending characteristics of the antenna at different bending degrees are analyzed. Measured results are in good agreement with simulations, which denotes that it is suitable for WLAN wireless systems.